2017
DOI: 10.3390/c3040029
|View full text |Cite
|
Sign up to set email alerts
|

Graphene–Noble Metal Nano-Composites and Applications for Hydrogen Sensors

Abstract: Graphene based nano-composites are relatively new materials with excellent mechanical, electrical, electronic and chemical properties for applications in the fields of electrical and electronic devices, mechanical appliances and chemical gadgets. For all these applications, the structural features associated with chemical bonding that involve other components at the interface need in-depth investigation. Metals, polymers, inorganic fibers and other components improve the properties of graphene when they form a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 38 publications
1
12
0
Order By: Relevance
“…To validate this explanation, the C1s XPS core-level spectrum of rGO is displayed in Figure 2 It results from the fact that Au ions in precursor solution often tend to bind with oxygen functional groups, which agglomerate at defect sites on the surface and the edges of GO sheets, via dangling bonds to form AuNP clusters during the reduction step. It is reported that there are differences of metal nanoparticles that interact with rGO sheets at different sites, i.e., the defective sites are more favorable compared to defect-free areas in the attachment of metal nanoparticles [1,10]. Considering the size of AuNPs, the AFM images reveal that sample A contains The peak movement results from the electron transfer from the rGO sheet to the AuNPs, indicating that an interaction exists between AuNPs and the rGO framework.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To validate this explanation, the C1s XPS core-level spectrum of rGO is displayed in Figure 2 It results from the fact that Au ions in precursor solution often tend to bind with oxygen functional groups, which agglomerate at defect sites on the surface and the edges of GO sheets, via dangling bonds to form AuNP clusters during the reduction step. It is reported that there are differences of metal nanoparticles that interact with rGO sheets at different sites, i.e., the defective sites are more favorable compared to defect-free areas in the attachment of metal nanoparticles [1,10]. Considering the size of AuNPs, the AFM images reveal that sample A contains The peak movement results from the electron transfer from the rGO sheet to the AuNPs, indicating that an interaction exists between AuNPs and the rGO framework.…”
Section: Resultsmentioning
confidence: 99%
“…In the past few years, reduced graphene oxide (rGO) has emerged as an alternative to graphene because it is possible to tailor and create "new functionalities" of graphene through defects and oxygen-containing functional groups [1]. Particularly for gas sensor applications, oxygen-related groups on the graphene surface are favorable for the adsorption of analytes, thus enabling detecting at lower concentrations of gases.…”
Section: Introductionmentioning
confidence: 99%
“…Heteroatom doping in graphene has many possible aspects like oxygen reduction reaction (ORR), hydrogen evolution reaction (HER) and oxygen evolution reaction which have been described by catalyst electrodes without any external support. 24 The heteroatoms doped in graphene materials are mainly covalently bonded to the carbon atoms of graphene. The extraordinary features of graphene such as high specic area, 3D conductive networks and porous structure allow the heteroatoms to be reliably and easily doped.…”
Section: Sensorsmentioning
confidence: 99%
“…The oxygen-containing groups can act as nucleation sites that anchor metal ions to facilitate the dispersion of metal NPs. [11][12][13] Graphenesupported metal NP composite materials have been used as chemical sensors, 14,15 electrodes for fuel cells 16 and other energy-related devices, [17][18][19] and as catalysts for hydrogenation reactions 20 and transformations of bio-based substrates. 11,21 The general route used to obtain metal NP-graphene composite materials involves the simultaneous reduction of metal salts adhered to or in proximity to the graphene oxide surface.…”
Section: Introductionmentioning
confidence: 99%